Feminist fabulation as refusal: Christine Yahya’s @pink_bits illustrating ‘bodies we are told to hide’ - Hickey-Moody, Anna Catherine; Willcox, Marissa Grace (Frontiers in Communication, 2025)
IntroductionDigital feminist fabulations offer a mode of resistance to algorithmic patriarchies that govern visibility and acceptability on social media platforms. Following Bergson (1932/1977) and Deleuze and Guattari (1994), and building on Haraway’s (2013, 2016) theorisation of fabulation as a practice of radical collective imagination, this study examines how feminist and queer visual cultures on Instagram respond to patriarchal censorship. Social media moderation policies often reproduce heteronormative, white, and able-bodied norms by restricting the visibility of diverse bodies and sexualities. In this context, feminist digital fabulation becomes a creative intervention into algorithmic injustice.MethodsThis paper draws on a four-year qualitative digital ethnography tracking the online practices of ten feminist and queer artists on Instagram. Data collection included longitudinal observation of public posts, artist statements, comment threads, and semi-structured interviews with each artist. The study focuses on the case of Christine Yahya (@pink_bits), a Sydney-based Armenian-Australian queer feminist artist and designer, to offer an in-depth analysis of one artist’s fabulatory resistance to platform regulation. Yahya’s work illustrates bodies and experiences marginalised in public discourse, including representations of disability, fatness, menstruation, masturbation, and mental illness.ResultsFindings indicate that Yahya’s art practice functions as a feminist digital fabulation in response to repeated shadowbanning and content removal on Instagram. Yahya creates stylised, illustrative representations of “bodies we are told to hide,” drawing attention to corporealities censored or invisibilised by content moderation systems. Rather than retreating in the face of moderation, Yahya transforms content reduction into a creative prompt. Her illustrations reimagine censored subjects as central, joyful, and unapologetically visible, working against the logics of algorithmic sorting and exclusion. These images do not only resist dominant visual cultures but actively produce alternative bodily imaginaries.DiscussionThis case study demonstrates how feminist digital fabulation operates as a creative political response to algorithmic governance. Yahya’s work offers a situated example of what Haraway (2016) calls “speculative fabulation” —a mode of world-building that defies normative constraints through collective reimagining. The practice of producing art that “troubles regulatory boundaries” generates a form of knowledge and critique that emerges within, and against, the infrastructures of platform capitalism. In doing so, Yahya’s digital art challenges the techno-patriarchal ideologies embedded in content moderation protocols and offers a vital feminist aesthetic that reclaims public visual space. This study contributes to cultural studies and digital media scholarship by theorising feminist fabulation as an embodied, affective, and strategic mode of resistance to algorithmic censorship.